Incompatible intravenous drug combinations and respective physician and nurse knowledge: a study in routine paediatric intensive care. Issue 4 (24th July 2017) - Neininger, Martina P; Buchholz, Patricia; Frontini, Roberto; Kiess, Wieland; Siekmeyer, Werner; Bertsche, Astrid; Siekmeyer, Manuaela; Bertsche, Thilo
Abstract : Objectives: To identify incompatible intravenous drug combinations in routine paediatric intensive care and evaluate physician and nurse knowledge. Methods: In a university paediatric intensive care unit, intravenous drug incompatibilities were analysed using a database and physician and nurse knowledge of incompatibilities was assessed using a questionnaire. Results: We analysed 665 prescriptions in 87 patients. Incompatible drug administration was identified in 9 (10%) of the 87 patients with a median of 3 different incompatibilities per patient (Q25/Q75: 1/3). We found 26 incompatible combinations. The most frequently involved drugs were cefotaxime, pantoprazole and vancomycin. A median of 10 of the 15 drug combinations were correctly assessed as compatible or incompatible (Q25/Q75: 8/11). Pantoprazole had a low number (20%) of correct answers. Conclusions: One in 10 patients in paediatric intensive care was affected by drug incompatibility, with knowledge deficits seen in a third of assessed combinations. This indicates quality improvement strategies should be urgently implemented by pharmacists.